PEDAGOGICAL DETERMINANTS OF BEHAVIOR IN THE STATUS OF A PROBLEM WHILE THE SHARE OF PHYSICAL EDUCATION AND SPORTS (WITH MYSELF AFTER STUDYING EDUCATION) - Karim Labane,; Fahssi Med Ryad,; Dr. Amrouche Mustapha, (Sport Scientific And Practical Aspects, 2025)
In light of changes in the teaching of physical education and sports field, we can talk about Alhdeddat to behaviors teaching for pupils to get to accomplish Activity kinesthetic proposal from the breeder party, and this is a plan searchof a scientific connotation explores all notices researcher through a network Note scientific tool. The goal of our research was to highlight the determinants of students to express behaviors that give the true picture of the creation of pedagogical interaction in order to solve a problem that characterize the status of a proposed pedagogical Gel. It has Touselnl to the presence of significant differences between the pupils who seem correlation between their behavior and pedagogical have the Breeder's quota in educational / learning